INTEGRATION OF MELUKAT AND COUNSELING GUIDANCE: EXPLORING THE POTENTIAL OF RITUAL FOR MENTAL HEALTH - Nursani, Rahma Naadira; Penulis, Ayu Sekar Wangi; Febiyanti, Dela; Syahrudi, Qonita; Asmara, Yuanisa Fatimada; Khusumadewi, Ari (PT Altin Riset Publishing, 2025)
This study aims to explore the tradition of malukat in Bali as a form of local wisdom that has therapeutic potential in supporting mental health, and to examine how this practice can be integrated into a multicultural guidance and counseling approach. The background of the study stems from the increasing interest of local and foreign tourists in the Malukat ritual, which is seen not only as a spiritual practice but also as a means of self-purification that provides inner calm and emotional balance. In the context of multicultural counseling, the counselor's understanding of the value and meaning of this tradition is considered important to increase the relevance and effectiveness of counseling interventions. This study used a qualitative method with a phenomenological approach, where data were collected through in-depth interviews, participatory observation, and documentation. The research subjects consisted of local people, foreign tourists, and counselors who understand multicultural practices. Data analysis was done thematically with coding, grouping, and meaning interpretation techniques, and data validation through source and method triangulation. The results showed that malukat provides psychological benefits in the form of decreased stress levels, increased sense of calm, and the formation of deep spiritual connections, both in local communities and foreign tourists. From a counseling perspective, malukat can be integrated as a culture-based approach that enriches multicultural counseling practices through symbols of purification, prayer, and self-reflection. Thus, the malukat tradition can be a bridge between local wisdom and modern counseling practices that emphasize cultural sensitivity and holistic healing.